Audiologists' perceptions of ethical climate and level of moral distress in the provision of amplification services in South Africa - Budden, Anne (Division of Communication Sciences and Disorders, 2025)
Moral Distress (MD) has attracted significant attention among researchers, with most research focused on nurses. South Africa has an unequal distribution of resources between the public and private healthcare sectors. Private practices depend on hearing aid sales to generate income, making the profession vulnerable to ethical concerns, which may affect the ethical climate and lead to MD. In public services provided by the state, audiologists have inadequate resources and funding; therefore, only some patients who warrant a hearing aid receive one, likely causing ethical and moral tensions. MD has negative consequences for professionals such as compassion fatigue, poor physical and psychological well-being, work dissatisfaction, turnover of staff, early retirement, and absenteeism. For patients, the consequences of MD can negatively influence service delivery, patient care, and satisfaction. Ethical climate or environment refers to shared perceptions of what is considered the right behaviour in an organisation when ethical standards need to be upheld and ethical reasoning is required. There is limited research on the level of MD among Hearing Healthcare Professionals (HHPs) and their perceptions of the ethical climate in their workplace, especially in developing countries, as most studies focusing on HHPs were conducted in well-resourced healthcare settings. This study aimed to close the gap in the literature and contribute to the existing global body of MD and ethical climate research among HHPs. An exploratory sequential, mixed-method approach was used to conduct a rigorous and methodologically sound study and reduced potential biases which arise from single data collection methods. Phase one included an online questionnaire consisting of a demographic questionnaire, the Moral Distress Appraisal Scale (MD-APPS), which measured the level of MD among HHPs, and the Ethics Environment Questionnaire (EEQ), which measured HHPs' perceptions of ethics within their workplace. Phase two comprised of online semi-structured interviews to obtain descriptive data about HHPs' perceptions and past experiences of MD and the ethical climate in their workplace. Quantitative data were analysed using one-way ANOVAS, linear regression tests, and Pearson correlation. Qualitative data were analysed via thematic analysis. Triangulation enabled the research question to be explored from different angles and strengthened the validity and reliability of the findings. Eighty-four HHPs completed the questionnaires, most of whom (59) worked in the private sector, and the remaining 25 worked in the public sector. The majority of respondents (44%) were relatively new to clinical practice with less than five years' experience. Seventeen participants participated in phase two. Again, most (14) worked in the private sector, of whom, five were private practice owners. Outcomes of the study indicate that most n=80 (80%) HHPs experienced no to mild levels of MD, and all HHPs perceived their ethical work environment as either neutral or positive. Interestingly, whether they worked in the public or private sector did not influence the ratings of ethical climates with a p-value of 0.1. Workload impacted perceptions of MD and ethics in the workplace, with participants experiencing high caseloads of (≥ 9 patients/ day) reporting higher levels of MD and perceived their work environment as poorer compared to those who saw between 0-5 and 6-8 patients per day. Most HHPs felt comfortable discussing their concerns with management and sought advice from colleagues rather than professional bodies. As expected, a negative linear relationship (r=-0.34) was found between MD and EEQ scores, therefore, participants who experienced higher levels of MD perceived their ethical work environments more poorly than those with lower MD scores. Age and gender did not impact levels of MD or the way in which HHPs perceived their ethical work environments; however, with more years of experience, participants reported lower levels of MD, which may suggest that work experience enables the development of moral resilience. HHPs with more work experience may also have a larger network of supportive colleagues. Work experience enabled HHPs to navigate ethical issues, while university ethics training was reported insufficient for the workplace. The interviews with respondents suggested that obstacles and external constraints which HHPs had to navigate included lack of support from professional bodies, disagreements clinical practice guidelines, expectations to achieve financial targets, and pressure to buy bulk and fit hearing instruments from certain hearing aid manufacturers. Issues related to patients concerned high caseloads, patient finances, and dealing with medical insurance companies. This research study explored MD levels among HHPs and the perceptions of their ethical work environment. Quantitative data showed HHPs experienced no to mild levels of MD and perceived their ethical work environment as neutral to positive; however, qualitative data raised additional concerns. For example, and of relevance for both training curricula and continuing professional education purposes, personal semi-structured interviews raised the need for more advanced ethics training to address dilemmas that are unique to the public and private healthcare sectors. This study hoped to start conversations with HHPs concerning MD and the ethical climate in their workplaces. Future research about MD interventions and ways to improve ethical climates could prevent adverse consequences as well as benefit HHPs and the population seeking hearing healthcare